Dinamika Sistem Pers di Indonesia - Inge Hutagalung (Master of Communication Science Program, Universitas Diponegoro, 2013)
Abstract:After the government ratifies law number 40 year 1999 Indonesia has applied the social responsibility theory of press. In the theory, press freedom has responsibility to public. Different from law number 11 year 1966 juncto law number 21 year 1982 that gave the authority to the government to control the press system, law number 40 year 1999 gives the authority to public.In facts in the context of freedom and commercialization,Indonesia’s press system has established media pluralism. It is the continuity of the New World Information and Communication Order. In the NWICO, it does not reflect media efforts to build public sphere since the last half of 1980 as the part of social responsibility in which ittrullyestablishes public freedom against the shackle of political and economic power.However, the Indonesian press industry has been in the domination of media conglomeration. Whether conscious or not, globally it is the part of penetration and expansion of capitalism and political power.Keywords: press system, social responsibility, media pluralism, media conglomeration, expansion of capitalism.Abstraksi :Di Indonesia, sejak pemerintah mengundangkan UU no 40 tahun 1999, secara normatif, pers Indonesia telah menganut teori pers tanggungjawab sosial (kebebasan pers yang bertanggung jawab pada masyarakat/kepentingan umum). Berbeda dengan UU no 11 tahun 1966 juncto UU no 21 tahun 1982 yang memberi kewenangan pada pemerintah untuk mengontrol sistem pers, UU no 40 tahun 1999 memberi kewenangan kontrol kepada masyarakat.Dalam pelaksanaannya, sistem pers Indonesia dewasa ini berada dalam kontek kebebasan dan komersialisasi yang telah menciptakan pluralisme media, yang pada hakekatnya merupakan kelanjutan Tata Komunikasi Dan Informasi Dunia Baru - dimana sejak paruh tahun 1980-an tidak lagi mencerminkan upaya media untuk membangun public sphere (sebagai bagian tanggung jawab sosial) yang benar-benar membebaskan masyarakat dari cengkraman kekuasaan: politik maupun ekonomi.Sistem pers yang ada dalam ranah media di Indonesia telah didominasi segelintir pemilik modal dalam industri pers Indonesia yang disadari atau tidak — juga merupakan bagian dari penetrasi dan ekspansi kapitalisme dan kekuatan politik secara global.Kata kunci: sistem pers tanggung jawab sosial, pluralisme media, dominasi pemilik modal, ekspansi kapitalisme.